Wireless technologies for Controlling a Traffic Lights Prototype - Cunha, João (2018)
This paper presents a traffic light control system based on wireless communication technologies. Traffic density is increasing at an alarming rate in developing countries which calls for intelligent dynamic traffic light control systems to replace the conventional manual and time based ones. The approach followed in this paper is based in a secure wireless sensor network to feed real time data to the intelligent traffic light control. A physical prototype was implemented for experimental validation. The physical prototype showed robustness against local failures or unforeseen cases showing that the communication between modules keeps an acceptable packets received ratio.